EKSPLOITASI GOA PINDUL SEBAGAI SPELEO TOURISM DI GUNUNG KIDUL, YOGYAKARTA - Kerti Pujani, Luh Putu; Kusuma Sanjiwani, Putri (Jurnal Analisis Pariwisata, 2017)
Indonesia has one of the three best points to enjoy the world-renowned Speleo Tourism, natural attraction Goa Pindul is one of the Kars Area which is included in Sewu Mountain UNESCO Global Geopark. Presenting a cave crash system, then causing natural attraction Goa Pindul become one tourist attraction that is dense tourist. The problem occurs when there is a negative impact of tourism in the form of natural exploitation. The problem raised in this research is how enforcement of environmental law is able to restore the function of nature and nature sustainability to the practice of exploitation of tourist attraction? This research uses the concept of policy, the concept of exploitation and the concept of tourist attraction. The results of this study indicate that the exploitation has a negative impact on the sustainability and sustainability of kars area. Environmental law enforcement through policy products in the form of Law on environmental protection, management and regulation to be able to run in synergy with nature conservation.